2016
DOI: 10.1016/j.bpsc.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Altered Functional Magnetic Resonance Imaging Activation and Cortical Thickness in Patients With Euthymic Bipolar I Disorder

Abstract: Background Performance during cognitive control functional magnetic resonance imaging (fMRI) tasks are associated with frontal lobe hypoactivation in patients with bipolar disorder, even while euthymic. Here, we study the structural underpinnings for this functional abnormality simultaneously with brain activation data. Methods In a sample of ninety adults (45 with inter-episode Bipolar I disorder and 45 healthy controls), we explored whether abnormal functional activation patterns in bipolar euthymic subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 99 publications
1
13
0
Order By: Relevance
“…In the present study, we observed cortical thickening in visual/somatosensory areas. Given that greater CT is commonly interpreted as better cortical integrity and has been positively related to cognitive function (33,35,38,(82)(83)(84)(85)(86)(87)(88)(89)(90)(91), it is tempting to speculate that cortical thickening reflects a structural normalization process. This line of reasoning is supported by results from our secondary analyses indicating that the increase of CT in visual/somatosensory areas may be related to lithium use.…”
Section: Longitudinal Cortical Changes In Bipolar Disordermentioning
confidence: 99%
“…In the present study, we observed cortical thickening in visual/somatosensory areas. Given that greater CT is commonly interpreted as better cortical integrity and has been positively related to cognitive function (33,35,38,(82)(83)(84)(85)(86)(87)(88)(89)(90)(91), it is tempting to speculate that cortical thickening reflects a structural normalization process. This line of reasoning is supported by results from our secondary analyses indicating that the increase of CT in visual/somatosensory areas may be related to lithium use.…”
Section: Longitudinal Cortical Changes In Bipolar Disordermentioning
confidence: 99%
“…Leaning on observations of previous studies providing important links between cortical thickness and neural activity in task relevant brain regions , the correlations observed could potentially reflect functional involvements, and the observed clusters might overlap with areas of regional activation. One could speculate that if a specific level of structural impairment is reached in a task relevant region (here medial prefrontal cortex), other brain regions might take a compensatory role (as possible in BDII).…”
Section: Discussionmentioning
confidence: 79%
“…The medial prefrontal cortex has been shown to be involved in response inhibition, inhibitory control, and task switching . Patients with bipolar disorder showed both hypoactivation during response inhibition and reduced thickness in (medial) prefrontal brain regions compared to controls . Interestingly, our explorative post hoc analyses of individual D‐KEFS subtests indicates that CWIT and TMT (i.e., tasks with a strong inhibition component) may be the tasks driving to the associations with medial prefrontal brain areas in controls and BDII (Figure ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations